Resolving Discrepancies in Forward and Reverse ABO Blood Group Typing - Kravhun, Pavlo Grigorovich; Korzh, Mykola Olexiyovich; Leontieva, Frida Solomonivna; Zinchenko , Olexandr Anatoliyovich; Lyzohub , Mykola Vitaliyovich; Dielievska, Valentyna Yuriivna (Scripta Medica, 2023)
Background/Aim: There is a need of investigation of high frequency of the cases of ABO discrepancy revealed by forward and reverse typing. The aim of the study was to reveal optimal methods for detection of weak subgroups of group A and B antigens on erythrocytes.Methods: Sixteen persons with A blood group and anti-B antibody adsorbing ability (weak Bel, Bm and B3 antigens), 5 persons with B blood group and anti-A antibody adsorbing ability (weak Ax antigen) and 2 persons with O blood group and anti-B antibody adsorbing ability (weak Bel antigen) were investigated as the cases of type II-III of ABO discrepancy and weak B antigen. Liquid chromatography, agglutination, inhibition of agglutination and adsorption reactions at 4 °C and 37 °C with prolonged incubation (12 hours) were used in the study.Results: The persons with A blood group revealed by forward typing at 4 °C and O blood group detected by reverse typing at 37 °C showed the ability of the erythrocytes to adsorb anti-B antibody. The persons with B blood group revealed by forward typing with presence of anti-B antibodies reactive at 37 °C showed the ability of erythrocytes to adsorb anti-A antibody. Prolonged incubation at reverse typing, adsorption-elution tests, inhibition of haemagglutination and liquid chromatography were used to define blood group specificity.Conclusion: Prolonged incubation during reverse typing at 4 °C and 37 °C, adsorption at 4 °C, heat elution and liquid chromatography might help to detect blood group type in cases of type II-III of ABO discrepancy.
Keywords: Chromatography; Antigen; Adsorption; Erythrocyte; Transfusion